Hubungan Pola Asuh Dan Fungsi Keluarga Dengan Tingkat Kecemasan Remaja Dalam Menghadapi Pembelajaran Daring Di Masa Pandemi Covid-19 Di SMA Negeri 2 Purwakarta - Shafiyyah Al Atsariyah (2021)
The transition of the learning process makes adolescents have to adapt to the environment that occurs, online learning has an impact on adolescents, one of which is anxiety, good parenting and family functions can reduce the level of anxiety felt by adolescents. This study aims to determine the relationship between parenting and family functions with adolescent anxiety levels in dealing with online learning during the COVID-19 pandemic at SMAN 2 Purwakarta. The method used is descriptive analytic with a cross-sectional approach. The sampling technique used was simple random sampling with a total sample of 260 adolescents. Data analysis used is univariate and bivariate analysis with Chi-Square test. The questionnaires used in this study were the Parental Authority Questionnaire (PAQ), Family Assessment Device (FAD), and Hamilton Anxiety Rating Scale (HARS). The results of this study indicate that there is a relationship between parenting and adolescent anxiety levels in dealing with online learning (p-value = 0.000) and there is a relationship between family function and adolescent anxiety levels in dealing with online learning (p-value = 0.000). Choosing the right parenting style and maximizing the dimensions of family function will affect the level of adolescent anxiety. Adolescent can discuss with their peers about material that is not understood, besides that they can tell their families and parents the obstacles they experience during online learning.